Preserving and enhancing the cultural landscape of Kampung Santubong, through eco-village approach / Hafizuddin Tajuddin, Faridatul Akma Abd Latif and Salina Mohamed Ali. - Tajuddin, Hafizuddin; Abd Latif, Faridatul Akma; Mohamed Ali, Salina (Universiti Teknologi MARA , Shah Alam: Faculty of Architecture, Planning and Surveying, 2018)
This article attempts to discuss a comprehensive design of landscape conservation for Kampung Santubong, Kuching Sarawak. The purpose study is by preserving and enhancing the cultural landscape of this village through eco-village approach. Major issue of the village is lack sense of personalization, damage of significant building, loss of traditional practice and loss of estuary mangrove ecosystem. As to encounter the issues, this study come out with the aims to revive the memory of Kampung Santubong by preserving and enhancing the local distinctiveness of Kampung Santubong through Eco-village approach. The methodology used in this project is by preparatory study from National Park Service (NPS) Guidelines for evaluating and documenting rural historic landscape and comparative study that reveals several design guidelines. Subsequently, the implications of the analysis and synthesis mapping is used to translate a complementary intervention proposed by the conceptual plan before developing a master plan. Based on this study, the sustainable design approach is used such as reef ball, river treatment, regreening, bio-pores and human and crocodile conflict management. The finding of the project is by preserving all the significant of Kampung Santubong through the identity and history of the village by interpreting the design with a sense of place while achieve balancing vernacular landscape. Hence, this study of cultural heritage village and design program as to sustain the cultural landscape at Kampung Santubong.